Ultrasound-Guided Fine-Needle Aspiration Versus Fine-Needle Capillary Sampling in Evaluation of Lymph Node Metastasis of Thyroid Cancer - Xia, Shujun; Chen, Yilai; Zhan, Weiwei; Zhou, Wei (Frontiers in Oncology, 2021)
Background:To compare the sampling adequacy and diagnostic efficiency of ultrasound-guided fine-needle aspiration with 22-, 25-gauge needles and capillary sampling with 22-gauge needle in the biopsy of cervical lymph node. Methods:A total of 130 cervical lymph nodes from 103 patients were consecutively included in the prospective study. Each suspected lymph node was aspirated with a 22-gauge needle, capillary sampled with a 22-gauge needle and aspirated with a 25-gauge needle. The adequacy rates and nondiagnostic rates of obtained specimen were calculated. Results: Of the 130 suspected lymph nodes, there were 77 lymph nodes＜6.0 mm and 53 lymph nodes≥6.0mm in the smallest dimension. Both FNA22G and FNC22G got significantly higher sampling adequacy than FNA25G for the total lymph nodes. For lymph nodes＜6.0 mm, the sampling adequacy was significantly higher with FNA22G than with FNA25G for each parameter and the cumulative score(all P＜ 0 .05), while no difference were seen between FNA22G and FNC22G, and between FNC22G and FNA25G.There were higher nondiagnostic rates for FNA25G compared with FNA22G and FNC22G in all lymph nodes and in each size subgroups. FNA25G yielded more diagnostically inadequate specimens than FNA22G and FNC22G did in the total lymph nodes (P=0.002), in lymph nodes＜6.0 mm (P=0.014), and in those≥6.0 mm (P=0.000). Conclusions: FNA22G and FNC22G obtained more diagnostically adequate specimens than FNA25G in cervical lymph nodes. FNA22G and FNC22G may be more suitable than FNA25G in diagnosing cervical lymph nodes. FNA22G and FNC22G may yield specimens with similar quality.